Cognitive Bahavioral Therapy In The Chronic Pain Management - GULCIN BABAOGLU; LEVENT ERTUGRUL INAN; KADIR OZDEL (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Pain is a complex experience that is influenced by neurological processes and psychosocial factors and important health problem that affects the individual, society, and work force, leading to reduced quality of life and physical activity and impaired social relations. Many studies have demonstrated the efficacy of cognitive behavioral therapy (CBT) in reducing the severity and frequency of pain, improving pain-induced negative mood, and improving quality of life. The patient's cognitive coping, cognitive restructuring, problem solving and relaxation skills are improved with CBT. Considering the biopsychosocial pain model and other literature information, chronic pain management should be organized in a multidisciplinary approach. [JCBPR 2017; 6(3.000): 133-140]